Efektivitas Penegakan Perda Kabupaten Buru No. 20 Tahun 2011 tentang Retribusi Pelayanan Persampahan dan Kebersihan bagi Masyarakat - darwin rukua (Jurnal Hukum Lex Generalis, 2025)
This study aims to evaluate the effectiveness of enforcing Buru Regency Regional Regulation No. 20 of 2011 on Waste Management and Sanitation Service Retribution. The research employed a qualitative approach with data collected through observation, interviews, questionnaires, and documentation. Data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the enforcement of the regulation has not been fully effective. Public understanding of the regulation remains relatively low due to limited socialization, differences in educational background, and a lack of legal literacy. Institutionally, the number of supervisory officers is inadequate, resulting in weak monitoring and sanction implementation. Limited facilities and infrastructure also hinder effectiveness; only six garbage trucks are available, whereas the ideal requirement is twelve units. This shortage leads to uneven service distribution, particularly in rural areas. The study concludes that the enforcement of the regulation is ineffective due to weak socialization, insufficient infrastructure, and low public compliance. It is recommended that the local government increase the intensity of socialization, improve service quality, provide adequate facilities and infrastructure, and strengthen collaboration with communities to achieve sustainable cleanliness and sanitation services in Buru Regency.